PEMANFAATAN PANGAN LOKAL DI PROVINSI NUSA TENGGARA TIMUR: Pengolahan Pangan Lokal Menjadi Tepung, Analisis Usaha dan Implikasi Kebijakannya - Yusuf Yusuf (Universitas Muhammadiyah Purwokerto, 2015)
Nusa Tenggara Timur (NTT) province identically with the dry land that had the potential of local food diversity both of tubers, cereal and fruits groups. Food processing based on local food, especially the tubers are still very limited in NTT. The objectives of this studi are (1) to determine the physico chemical characteristics of modified cassava flour (mocaf), sweet potato flour and corn flour, (2) to determine the financial feasibility of mocaf, sweet potato flour and corn flour in Timor Tengah Selatan regency, NTT. Introduction approach of processing through the understanding and skills of processing of mocaf, sweet potato flour and corn flour in two women farmers groups (KWT), namely KWT Suka Maju Ajaobaki Village Mollo Utara District and KWT Hetven Kesetnana village Mollo Selatan District, Timor Tengah Selatan regency. Introductions of processing technology has been done after optimization of the processing in the Laboratory of BPTP NTT. The results showed that the local food such as cassava, sweet potato and corn can be processed into flour so can increase the added value and increase the competitiveness of local food. Local food flour can be used as a wheat flour substitute in food processing. Flouring effort of mocaf, sweet potatoes and corn had been managed efficiently indicated by revenue cost ratio (RCR) value is more than 1.00.